Study on the relationship between intrapartum group B streptococcus prophylaxis and food allergy in children - Zhang, Hong; Xu, Kang; Liu, Zhihui; Shi, Yuanmei; Li, Hui; Yin, Xiaoping (Frontiers in Pediatrics, 2022)
Objective: To investigate the associations between intrapartum antibiotic prophylaxis of group B streptococcus (GBS) in pregnant women and the risk of food allergy in Chinese children Design: Retrospective cohort study of 2909 mother-child pairs. Setting: Taixing People's Hospital in Eastern China. Participants: Term infants born 2018-2019, followed longitudinally from birth to 3 years. Exposures: The GBS-IAP was defined as therapy with intravenous penicillin G or ampicillin or cefazolin ≥4 hours prior to delivery to the mother. Reference infants were defined as born without or with other intrapartum antibiotic exposure. Methods: To investigate the incidence information of food allergy in children aged 18 months and three years old. Kaplan-Meier survival analysis and log-rank tests were used to evaluate the cumulative incidence in the group with GBS-IAP and the group without GBS-IAP. Cox proportional hazards models were conducted to determine the univariate and multivariate association between maternal GBS-IAP and incident food allergy after various covariates were adjusted. Results: The cumulative incidence of food allergy in the group with GBS-IAP was higher than that in the group without GBS-IAP in children under 18 months old (8.1% vs. 4.5%, P=0.005,log-rank test), but no significant differences were observed in children under three years old (9.2% vs. 7.0%, P=0.146,log-rank test). The univariate cox proportional hazards model in children under 18 months old revealed that children in the GBS-IAP group had faster food allergy development when compared with children in the group without GBS-IAP (HR.: 1.887,95% CI: 1.207-2.950, P=0.005), so was the multivariate model (HR.: 1.906,95% CI: 1.158-3.137, P=0.011). However, both univariate (HR：1.343，95% CI：0.891~2.026， P=0.159) and multivariate (HR：1.253，95%CI：0.796~1.972， P=0.329) cox proportional hazards model in children under three years old showed no significant differences between children in the group with GBS-IAP and group without GBS-IAP. Conclusion: Intrapartum antibiotic prophylaxis of group B streptococcus may increase the cumulative incidence and risk of food allergy in children under 18 months old, but it had no significant effect on children under three years old.